2015
DOI: 10.5902/2179460x20842
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Simulation of Control System for Pneumatic Servo Valve Using Piezoelectric Actuator

Abstract: In this study design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The analysis of overshoot ( ) also revealed that PFC consistently provided 0 % of , for all the positioning distances. Considering that the overshoot in the transient response of the pneumatic system was mainly due to the compressibility of air [11], the maximum allowable overshoot for this study was set to 10 % as similarly used in other studies [24], [25]. Although there was a slight overshoot at the beginning of the positioning response (for all positioning distances) using CMPC; however, it is considered acceptable to control the pneumatic positioning system since it manages to provide <10 % of overshoot for all positioning distances.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of overshoot ( ) also revealed that PFC consistently provided 0 % of , for all the positioning distances. Considering that the overshoot in the transient response of the pneumatic system was mainly due to the compressibility of air [11], the maximum allowable overshoot for this study was set to 10 % as similarly used in other studies [24], [25]. Although there was a slight overshoot at the beginning of the positioning response (for all positioning distances) using CMPC; however, it is considered acceptable to control the pneumatic positioning system since it manages to provide <10 % of overshoot for all positioning distances.…”
Section: Resultsmentioning
confidence: 99%